BH2Cl دراسة الخواص الحرارية والطيفية لجزيئة - عبد المنعم, عدي مازن (Al-Nahrain Journal of Science, 2018)
Abstract:A theoretical study by using series of software that associated with molecular pattern for spectroscopic and thermal characteristics for BH2Cl has been done, and drawing potential energy curve for molecule with variation of band length between B-Cl, from which the calculation of the spectral dissociation energy which was found to be (De=2.45eV), Also the molecular disintegration has been studied , and its frequency that take place and its active value at Raman spectrum and I.R due to the variations in polarization and diapole moment for molecular.On theother hand, the thermodynamic characteristics, and its value at room temperature (298 k) where the heat of Formation (∆H˚f=-24.8kcal/mol), Enthalpy (H=-2478.2cal/mol), Heat Capacity (CP=13.63cal/K.mol), Entropy (S=56cal/K.mol) and the value of this characteristics have been calculated at different temperature from (100-3000K), and every characteristic was drawn with temperature finally, the bond length B-Cl has been calculated and its value (1.75608Å), and all the results in this research was approached to the previous work .